"Can't live willingly": A thematic synthesis of qualitative evidence exploring how early marriage and early pregnancy affect experiences of pregnancy in South Asia. - Faith A Miller; Sophiya Dulal; Anjana Rai; Lu Gram; Helen Harris-Fry; Naomi M Saville (Public Library of Science (PLoS), 2023)
In South Asia, early marriage has been associated with a range of adverse outcomes during pregnancy and infancy. This may partly be explained by early marriage leading to a younger maternal age, however it remains unclear which other factors are involved. This review aimed to synthesise the qualitative evidence on experiences of pregnancy following early marriage or early pregnancy in South Asia, to inform our understanding of the mechanisms between early marriage and adverse pregnancy outcomes. We searched MEDLINE, EMBASE, Scopus, Global Index Medicus, CINAHL, PsycINFO, Web of Science, and grey literature on 29/11/2022 to identify papers on experiences of pregnancy among those who married or became pregnant early in South Asia (PROSPERO registration number: CRD42022304336, funded by an MRC doctoral training grant). Seventy-nine papers from six countries were included after screening. We appraised study quality using an adapted version of the Critical Appraisal Skills Programme tool for qualitative research. Reporting of reflexivity and theoretical underpinnings was poor. We synthesised findings thematically, presenting themes alongside illustrative quotes. We categorised poor pregnancy experiences into: care-seeking challenges, mental health difficulties, and poor nutritional status. We identified eight inter-connected themes: restrictive social hierarchies within households, earning social position, disrupted education, social isolation, increased likelihood of and vulnerability to abuse, shaming of pregnant women, normalisation of risk among younger women, and burdensome workloads. Socioeconomic position and caste/ethnic group also intersected with early marriage to shape experiences during pregnancy. While we found differences between regions, the heterogeneity of the included studies limits our ability to draw conclusions across regions. Pregnancy experiences are largely determined by social hierarchies and the quality of relationships within and outside of the household. These factors limit the potential for individual factors, such as education and empowerment, to improve experiences of pregnancy for girls married early.